Rheumatology and Neurology. Issue 3 (June 2017) - Dimberg, Elliot L.
Abstract : ABSTRACT: Purpose of Review: This article reviews the various rheumatologic disorders that have neurologic complications and manifestations. Recent Findings: Recent advances have improved the understanding of the true epidemiology of many rheumatologic diseases and their complications. Many years of observation have clarified findings even in rarer disorders. Classification and diagnostic criteria have been updated and validated. As newer pharmacologic agents have become available, new information regarding efficacy and toxicity has emerged. Summary: Rheumatologic disorders are common, as can be their neurologic complications. In many instances, these complications are treatable, but clinicians' understanding of the underlying disorder, its neurologic risks, and the risk of therapy is required.